Ln(-7x+3)=-1

Simple and best practice solution for Ln(-7x+3)=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Ln(-7x+3)=-1 equation:


Simplifying
Ln(-7x + 3) = -1

Reorder the terms:
nL(3 + -7x) = -1
(3 * nL + -7x * nL) = -1
(3nL + -7nxL) = -1

Solving
3nL + -7nxL = -1

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Reorder the terms:
1 + 3nL + -7nxL = -1 + 1

Combine like terms: -1 + 1 = 0
1 + 3nL + -7nxL = 0

The solution to this equation could not be determined.

See similar equations:

| 3zx+6=12 | | 3(3u-1)=-31 | | -11/12-(5/8) | | 72=2(l+l-w) | | 6n^2+11n-95=0 | | 180-3x=6x | | .4x+.7y=.5*20 | | 3m+7(m+7)=89 | | 2n^2+2=10n | | 4c^3-1c=0 | | 9-16+6x=11x+4x-5 | | 4u+5u+4u=p+q | | 3x^2-21x^6=0 | | Y-1=4y-10 | | 3(-5)+2=5 | | X^2-5p=0 | | 2x^4+5x^2-12=0 | | 5/8-(5/6) | | 17x^2-12xy+8y^2-22x-4y+14=0 | | 3(x+y)-r=2y | | B^2-2b+7=0 | | 2z=14-20 | | 4x-30+3x=180 | | 12x-14=70+9x | | X-1/6=23/6 | | y(n)-0.5y(n-1)=x(n)+x(n-1) | | -54-17x=90-14x | | 12x-14=50+9x | | (x^4/8)^3 | | 108-2x=4y | | 2y+3=-3y-7 | | m^2+16m+4=0 |

Equations solver categories